2007
DOI: 10.1007/s00381-007-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy in children younger than 2 years of age

Abstract: The success of ETV in children younger than 2 years of age suffering from non-communicating hydrocephalus seems to be dependent on both age and etiology. Our results show an overall success rate of 43%. In 37.5% of the children younger than 1 year of age, ETV was successful. ETV in patients with hydrocephalus due to idiopathic aqueductal stenosis seems to be more beneficial than in other causes of hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
70
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 25 publications
6
70
0
2
Order By: Relevance
“…In both congenital and acquired stenosis of the aqueduct, Jones et al [13,29] and, more recently, Mugamba and Stagno [13,29] reported high success rates that were related to the acquired type, the age at symptom onset and the surgical procedure [13,70,71]. Similarly, in our series, we found a success rate among adults of 87.5%, which is similar to that reported in more recent studies [13,56].…”
Section: Discussionsupporting
confidence: 91%
“…In both congenital and acquired stenosis of the aqueduct, Jones et al [13,29] and, more recently, Mugamba and Stagno [13,29] reported high success rates that were related to the acquired type, the age at symptom onset and the surgical procedure [13,70,71]. Similarly, in our series, we found a success rate among adults of 87.5%, which is similar to that reported in more recent studies [13,56].…”
Section: Discussionsupporting
confidence: 91%
“…While some authors reported no correlation of hydrocephalus etiology with ETV outcomes, 3,8,19,21 others have found etiology to be predictive of ETV success. 1,9,10 Etiology of hydrocephalus accounts for up to 33% of the possible points in the aforementioned ETV success score paradigm. 10 A notable limitation of administrative databases, the MarketScan database included, is that ICD-9 coding with insurance claims may not be as reliable in classifying diagnoses as clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other smaller studies have reported conflicting information on the role of age, etiology, and other factors on the impact of success after ETV. 1,8,9,15,19 Kulkarni et al described multinational series; predictive strategies have been used to create success scores for various populations. 10,11,25 However, it remains to be seen if a national sample has similar ETV success compared with these site-specific studies.…”
mentioning
confidence: 99%
“…Reports have indicated that outcome is a function of age 23,32,33 independent of age, 1,34 a function of etiology, 1,35-37 or a function of both age and etiology. 38 More recent evidence from larger, and in one case, multicenter series has supported the finding that age is the main determinant of outcome with younger children, particularly neonates, faring worse. 39,40 The other standard technique of CSF diversion, a CSF shunt, has rarely been compared with ETV, with results suggesting no difference 41 or a slight advantage in terms of costeffectiveness for ETV.…”
Section: Discussionmentioning
confidence: 87%